Tourism and power plants as aids in regional development - Sæþórsdóttir, Anna Dóra; Stefánsson, Þorkell (Research in applied business and economics, 2017)
Opportunities in the tourism industry along with the harnessing of energy resources are commonly referred to as means of dealing with changes in employment structure, to counteract depopulation in rural areas, and as a way to create capital. Both fields utilize nature as a resource, but can they coexist or are conflicts foreseeable? In order to find out whether the tourist industry consider that proposed power plant developments will diminish the possibilities of the tourism sector to strengthen local settlements semi-structured interviews were conducted with 65 tourist service providers in six different parts of Iceland. In the opinion of the interviewees the tourism sector is the industry that offers the best long-term possibilities to strengthen the economy in rural areas and most of them had seen clear indications of this in recent years. Many interviewees felt that energy production and tourism do not concur because the negative effects energy production can have on nature, the core resource for the tourist industry. Uncertainty over where power developments will be located was thought to have delayed investment and marketing efforts in certain areas. A few of the interviewees mentioned examples of successful cohabitation of energy production and tourism and it was pointed out that favourable collaboration between the two industries could diminish their conflict of interest. Moreover, it was stated that the income from both industries could reach the areas where it was generated more effectively. Tækifæri á sviði ferðaþjónustu og nýtingar orkuauðlinda eru oft nefnd sem leiðir til þess að takast á við breytta atvinnuhætti, sporna við fólksfækkun í dreifbýli og skapa verðmæti. Báðar greinarnar nýta náttúruna sem auðlind en geta þær farið saman eða eru fyrirsjáanlegir hagsmunaárekstrar milli þeirra? Til þess að komast að því hvort ferðaþjónustuaðilar telji fyrirhugaðar virkjunarhugmyndir rýra möguleika ferðaþjónustunnar til að efla byggð í landinu voru tekin hálfstöðluð viðtöl við 65 ferðaþjónustuaðila á sex ...